Логічний квадрат, його можливості у визначенні істинності або хибності суджень - Малахова, О. Ю. (ХНУРЕ, 2021)
The rules of the "logical square" are the basis for constructing inferences, which, in turn, underlie any reasoning. In order to have a clearer idea of how to conduct one's opinion, so as not to violate generally accepted logical laws, it seems necessary to go from the origins, and to study the rules of the "logical square", which were formulated in ancient times, but have not lost their relevance and to this day.
Keywords: філософія; логічний квадрат